Epilepsy Surgery and Tuberous Sclerosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
The results of operation for treatment of epilepsy in 5 male and 4 female patients with tuberous sclerosis (TSC) in a 5-year period from 1986-1990 are reported from the Mayo Clinic.